Cellular Ageing and Replicative Senescence - Rattan, Suresh I.S; Hayflick, Leonard (Healthy Ageing and Longevity, 2016)
This book covers the origins and subsequent history of research results in which attempts have been made to clarify issues related to cellular ageing, senescence, and age-related pathologies including cancer. Cellular Ageing and Replicative Senescence revisits more than fifty-five years of research based on the discovery that cultured normal cells are mortal and the interpretation that this phenomenon is associated with the origins of ageing. The mortality of normal cells and the immortality of cancer cells were also reported to have in vivo counterparts. Thus began the field of cytogerontology. Cellular Ageing and Replicative Senescence is organized into five sections: history and origins; serial passaging and progressive ageing; cell cycle arrest and senescence; system modulation; and recapitulation and future expectations. These issues are discussed by leading thinkers and researchers in biogerontology and cytogerontology. This collection of articles provides state-of-the-art information, and will encourage students, teachers, health care professionals and others interested in the biology of ageing to explore the fascinating and challenging question of why and how our cells age, and what can and cannot be done about it.